If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(7 + -1n) = 12 (7 * 12 + -1n * 12) = 12 (84 + -12n) = 12 Solving 84 + -12n = 12 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + -12n = 12 + -84 Combine like terms: 84 + -84 = 0 0 + -12n = 12 + -84 -12n = 12 + -84 Combine like terms: 12 + -84 = -72 -12n = -72 Divide each side by '-12'. n = 6 Simplifying n = 6
| 4a+17=7+2a | | 2n^2+3n+9=0 | | -9y-10=62 | | 50x+43200=45675-175x | | y=-0.109(2060)+244.607 | | 7(7+2m)+6m=169 | | 410=115+60x | | -4.3+12+15.1c=33.6c | | -2(-3w+v-5)= | | k+8=10+7p | | 6(x+6)=2(x+28) | | 4y-14=2 | | 4.8n+5=4.8n+5 | | 4x=167 | | 6r+8r=16-2r | | c+(-2)=-0.7 | | 10x+(-x)+(-21)=0 | | -5-6k=3k-14 | | z/(-2)+5=7 | | 5000000*12*1/5280*1/.621=x | | 9+c=2c | | 22=20+B | | 4+6x=6+2x | | 4a+17=11(a+2) | | 7-8a=4-7a | | -5x-2(-4x+16)=56 | | 9c+c=2c | | 7d-2=12 | | y=0.15x(x-8) | | -7d-8+2(d+12)=52 | | m-4=-6m-11 | | x+(13x+34)=90 |